What's the Worst Thing You Can Do to Shakespeare? - Hedrick, Donald (My University, 2018)
To judge by its cover, this book is a mess — a deliberately instructive one. Its visuals combine an eroded font as well as an ink-splattered Shakespeare signature and an Etch A Sketch incongruously displaying Shakespeare’s Chandos portrait. The media mix embodies the authors’ provocative approach: Shakespeare as “multimedia archive” — Latour’s “iconoclash” of time-spanning formats in material “substrates” of texts, media, and human “wetware.” The Folio’s “media launch” by Shakespeare’s friends cannily initiated a fetish community around the “strategically imperfect” object’s gaps, urging us to read “him” — book and man composite “bio-bibilion” — “again and again.” The “worst” becomes not reading him, the condition defining the “unreadable” spaces made visible in adaptations. The study deconstructs dazzlingly, drawing readers into the brilliant, imitative high spirits of the authors’ animated, collaborative anonymity; their playful preface even occludes which coauthor speaks. Chapter transitions imitate radio or telephone: Hamlet’s ends with a “call coming through” from the next chapter’s Juliet (45). Their introduction highlights foundational scholarship for their project: McCleod on unediting; de Grazia undoing Hamlet’s post-romantic rebranding; Middleton’s authorship now altering Shakespeare’s “gravitational field”; Stallybrass’s and Lesser’s recovery of reading for sententiae, so that Hamlet was “never read”; Eagleton’s apocalyptic “worst” — that Shakespeare must be destroyed before becoming readable again.
Citation: Hedrick, D. (2016). What's the Worst Thing You Can Do to Shakespeare? Renaissance Quarterly, 69(3), 1196-1197. Retrieved from https://doi.org/10.1086/689159
Keywords: Arts & Humanities - Other Topics